SISTEM INFORMASI MONITORING PERBAIKAN MOBIL PADA PT TOYOTA ASTRA MOTOR CIBITUNG BERBASIS WEB - Nurfauziah, Habibah; Gunadis, Soni Perdana (Universitas Dirgantara Marsekal Suryadarma, 2020)
The significant increase in National Market Growth from year to year has triggered an increase in Toyota vehicle sales targets in the area of each branch throughout Indonesia. In general, it has an impact with an increase in the amount of capacity and delivery process at PT Toyota Astra Motor (TAM) Cibitung. This includes potential defective units which are caused during the handover process or the shipping transportation process. So that units that undergo repairs must be quickly followed up, full supervision and immediate repair or replacement of spare parts. Based on observations made by the author, it is found that the process of monitoring car repairs is still done manually and the operators are not always ready to monitor the unit because of the many other jobs that must be done. So we need a tool that can help monitor the repair unit. With the hope of helping the process of monitoring improvements in the company to be more effective, efficient, safe and comfortable.Â Keywords: Information Systems, Car Repair Monitoring, Web